Comparing time-series transcriptomes between chilling-resistant and -susceptible rice reveals potential transcription factors responding to chilling stress - Zhang, Rui; Xi, XiaoHui; Chen, XinYi; Wang, Yi; Zhou, Ming (Frontiers in Plant Science, 2024)
Low temperature is one of the most important environmental factors that inhibits rice growth and grain yield. Transcription factors (TFs) play crucial roles in chilling acclimation by regulating gene expression. However, transcriptional dynamics and key regulators responding to low temperature remain largely unclear in rice. In this study, a transcriptome-based comparative analysis was performed to explore genome-wide gene expression profiles between a chilling-resistant cultivar DC90 and a chilling-susceptible cultivar 9311 at a series of time points under low temperature treatment and recovery condition. A total of 3,590 differentially expressed genes (DEGs) between two cultivars were determined and divided into 12 co-expression modules. Meanwhile, several biological processes participating in the chilling response such as abscisic acid (ABA) responses, water deprivation, protein metabolic processes and transcription regulator activities were revealed. Through weighted gene co-expression network analysis (WGCNA), 15 hub transcription factors involved in chilling conditions were identified. Further, we used the gene regulatory network (GRN) to evaluate the top 50 TFs, which might have potential roles responding to chilling stress. Finally, 5 TFs, including a C-repeat binding factor (OsCBF3), a zinc finger-homeodomain protein (OsZHD8), a tandem zinc finger protein (OsTZF1), carbon starved anther (CSA) and indeterminate gametophyte1 (OsIG1) were identified as crucial candidates responsible for chilling resistance in rice. This study deepens our understanding in the gene regulation networks of chilling stress in rice, and offers potential gene resources for breeding climate-resilient crops.